Fast uptake of organic pollutants from dilute aqueous solutions by nanoporous-crystalline PPO films with c-perpendicular orientation. (5th December 2021) - Cozzolino, Antonietta; Nagendra, Baku; Rizzo, Paola; Daniel, Christophe; Guerra, Gaetano
Graphical abstract: Highlights: Polymer films for water decontamination from organic pollutant traces. Higher pollutant uptakes by PPO crystalline rather than by PPO amorphous films. Kinetics of pollutant uptakes depending on nanoporous-crystalline phase orientation. Fast pollutant uptakes for crystalline chain axes perpendicular to the film plane. Abstract: The extraordinary ability of poly(2, 6-dimethyl-1, 4-phenylene)oxide (PPO) dense films, exhibiting a nanoporous-crystalline (NC) phase, to absorb traces of organic pollutants dissolved in water is shown. Equilibrium uptakes and sorption kinetics of perchloroethylene (PCE) are much higher and faster than for the corresponding amorphous films. For sorption kinetics, particularly relevant is a control of the planar orientation of the NC phase. For instance, for PCE sorption from 50 ppm aqueous solutions, a NC α form film with orientation of the crystalline polymer chains being preferentially perpendicular to the film plane ( c ⊥ orientation) exhibit a diffusivity nearly 14 times higher than for a NC film with crystalline polymer chains being preferentially parallel to the film plane (c// orientation) and nearly 88 times higher than for the starting amorphous PPO film. This phenomenon is rationalized in terms of crystalline channels being preferentially perpendicular to the film plane. Moreover, equilibrium uptakes for NC PPO films are much higher than for NC sPS films. For instance, for sorption experiments from PCE 50 ppm aqueous solutions, equilibrium uptakes for NC PPO and sPS films are nearly 15 wt% and 2 wt%, respectively. This phenomenon is rationalized by the high-free volume of both NC and amorphous phases of PPO.